TAXONOMIC CHARACTERIZATION OF TWO SPECIES OF THE GENUS SESBANIA FABACEAE FROM THE STATE OF PUNJAB, INDIA - Rai Singh Dhillon, Harpreet Kumar, Vanshpreet Singh, (EPRA International Journal of Research and Development (IJRD), 2023)
Present study is conducted in the district Faridkot, Punjab India during paddy season in the year 2023. Two species of the genus Sesbania viz. S. sesban (L.) Merr. and S. bispinosa (Jacq.) W. Wight. are collected from the study area. Sesbania bispinosa is a weed species of different kharif crops such as rice, maize, sorghum and cotton. Sesbania sesban is generally grown as a green manure crop in the study area. Morphological parameters (stem, leaf, flower, androecium, gynoecium, fruit, seed, etc.) of these species were examined for proper identification. Present findings will be useful for researchers, botanists, ethnobotanists accurate identification of Sesbania species.